Cell-bound nanoparticles for tissue targeting and immunotherapy: Engineering of the particle–membrane interface. (April 2021) - Prakash, Supriya; Kumbhojkar, Ninad; Clegg, John R.; Mitragotri, Samir
Abstract: Nanoparticles (NPs) have been developed as vehicles for delivering a variety of payloads including small molecules, nucleic acids, and proteins. To overcome the non-specific biodistribution of nanomaterials and target specific sites in vivo, there has been a surge of interest in using autologous cells as NP carriers. To design cell– NP constructs for active targeting, an understanding of the physicochemical interactions that underline NP adhesion, detachment, and uptake is necessary. In this article, we critically analyze the various properties that affect cell–nanomaterial interactions. We describe how physical properties of the cellular plasma membrane such as curvature, membrane tension, and lipid composition affect the attachment of NPs. We discuss the effect of NP properties including size, shape, stiffness, and chemical composition as well as the environmental conditions on the cell–NP interactions. We conclude with an overview of recent applications of cell–NP constructs including cellular hitchhiking, backpacking, and responsive surface attachment for drug delivery.